Hydrolysis and fermentation steps of a pretreated sawmill mixed feedstock for bioethanol production in a wood biorefinery. (August 2020) - Abdou Alio, Maarouf; Tugui, Oana-Cristina; Rusu, Lacramioara; Pons, Agnès; Vial, Christophe
Highlights: Microwave-based Organosolv pretreatment is efficient for wood biomass fractionation. Pretreated sawmill mixed feedstock (71% w/w cellulose) was enzymatically hydrolyzed. Up to 80% cellulose-to-glucose conversion yield was achieved. 16 g/L of ethanol was produced from 34.5 g/L sugars (80% of the theoretical yield) Glucose production during saccharification could be accurately modelled. Abstract: The aim of this work was to demonstrate the feasibility of second-generation bioethanol production using for the first time a sawmill mixed feedstock comprising four softwood species, representative of biomass resource in Auvergne-Rhône-Alpes region (France). The feedstock was subjected to a microwave-assisted water/ethanol Organosolv pretreatment. The investigation focused on enzymatic hydrolysis of this pretreated sawmill feedstock (PSF) using Cellic® Ctec2 as the enzyme, followed by fermentation of the resulting sugar solution using Saccharomyces cerevisiae strain. The cellulose-rich PSF with 71% w/w cellulose content presented high saccharification yields (up to 80%), which made it perfect for subsequent fermentation; this yield was predicted vs. time up to 5.2% w/v PSF loading using a mathematical model fitted only on data at 1.5%. Finally, high PSF loading (7.5%) and scaleup were shown to impair the saccharification yield, but alcoholic fermentation could still be carried out up to 80% of the theoretical glucose-to-ethanol conversion yield.